A Multimodal Critical Discourse Analysis of “The Marvels” Movie Poster - Budiastono, Herning; Romel Noverino (International Journal of English and Applied Linguistics (IJEAL), 2024)
Movie posters are not only used as a tool of artistic purposes, but also are essential elements within the extensive realm of film marketing, serving as visual representatives that are intended to charm and attract potential viewers. This research aims to provide a comprehensive understanding of how linguistic and multimodal elements intersect in the analysis of movie posters used in as a film promotion tool. This study uses Kress and van Leeuwen multimodal discourse analysis theory to discuss the findings carried out on The Marvels movie poster, which aim to reveal how verbal and visual signs work together as social sign to interpret the representational, interactional, and compositional meanings. The research uses Teun A. van Dijk multimodal dimension, which includes analyse a thorough review of visual components, design decisions, and symbolic depictions to understand their intended effect on prospective audiences. Moreover, this investigation unveiled the subtle ways in which societal, cultural, and cognitive factors impact interpretation. Delving into the social cognitive dimension within these posters provides insights into how audience reception is shaped by cultural contexts and cognitive mechanisms. The study stands as a testament to the interdisciplinary nature of research in linguistics and semiotics within the realm of visual communication.